Climate change will decrease the range size of snake species under negligible protection in the Brazilian Atlantic Forest hotspot - Lourenço-de-Moraes, Ricardo; Lansac-Toha, Fernando Miranda; Schwind, Leilane Talita Fatoreto; Arrieira, Rodrigo Leite; Rosa, Rafael Rogério; Terribile, Levi Carina; Lemes, Priscila [UNESP]; Fernando Rangel, Thiago; Diniz-Filho, José Alexandre Felizola; Bastos, Rogério Pereira; Bailly, Dayani (Springer Nature, 2019)
Reptiles are highly susceptible to climate change, responding negatively to thermal and rainfall alterations mainly in relation to their reproductive processes. Based on that, we evaluated the effects of climate change on climatically suitable areas for the occurrence of snakes in the Atlantic Forest hotspot, considering the responses of distinct reproductive groups (oviparous and viviparous). We assessed the species richness and turnover patterns affected by climate change and projected the threat status of each snake species at the end of the century. We also evaluated the effectiveness of the protected areas in safeguarding the species by estimating the mean percentage overlap between snake species distribution and protected areas (PAs) network and by assessing whether such areas will gain or lose species under climate change. Our results showed greater species richness in the eastern-central portion of the Atlantic Forest at present. In general, we evidenced a drastic range contraction of the snake species under climate change. Temporal turnover tends to be high in the western and north-eastern edges of the biome, particularly for oviparous species. Our predictions indicate that 73.6% of oviparous species and 67.6% of viviparous species could lose at least half of their original range by 2080. We also found that existing protected areas of the Atlantic Forest Hotspot have a very limited capacity to safeguard snakes at the current time, maintaining the precarious protection in the future, with the majority of them predicted to lose species at the end of this century. Although oviparous and viviparous snakes have been designated to be dramatically impacted, our study suggests a greater fragility of the former in the face of climate change. We advocated that the creation of new protected areas and/or the redesign of the existing network to harbour regions that maximize the snake species occupancy in the face of future warming scenarios are crucial measures for the conservation of this group.